Stem Cells and Innate Immunity in Aquatic Invertebrates: Bridging Two Seemingly Disparate Disciplines for New Discoveries in Biology - Ballarin, Loriano; Karahan, Arzu; Salvetti, Alessandra; Rossi, Leonardo; Manni, Lucia; Rinkevich, Baruch; Rosner, Amalia; Voskoboynik, Ayelet; Rosental, Benyamin; Canesi, Laura; Anselmi, Chiara; Pinsino, Annalisa; et al. (Frontiers in Immunology, 2021)
The scopes related to the interplay between stem cells and the immune system are broad and range from the basic understanding of organism’s physiology and ecology to translational studies, further contributing to (eco)toxicology, biotechnology, and medicine as well as regulatory and ethical aspects. . Stem cells originate immune cells through hematopoiesis and the interplay between the two cell types is required in processes like regeneration. In addition, stem and immune cell anomalies directly affect the organism’s functions, its ability to cope with environmental changes and, indirectly, its role on ecosystem services. However, stem cells and immune cells continue to be considered parts of two branches of biological research with few interconnections between them. This review aims to bridge these two seemingly disparate disciplines towards much more integrative and transformative approaches with examples deriving mainly from aquatic invertebrates. We discuss the current understanding of cross-disciplinary collaborative and emerging issues, raising novel hypotheses and comments. We also discuss the problems and perspectives of the two disciplines and how to integrate their conceptual frameworks to address basic equations in biology in a new, innovative way.